LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENGEMBANGKAN REGULASI DIRI SISWA KELAS VIII - Ahmad Habibi (Empati-Jurnal Bimbingan dan Konseling, 2019)
This study aims to determine the effect of group guidance services with self management techniques to develop self-regulation in students. This type of research is quantitative research through true experimental design research method with a pre-test post-test control group design model. The population in this study were 178 students. The sample in the study were 20 eighth grade students of Muhammadiyah 3 Junior High School Semarang who were taken using simple random sampling technique. The data collection tool used is the scale of self regulation. Based on the results of the hypothesis test analysis obtained the results of t count tcount = 4.28. Then consulted with ttable with a significance level of 5% (0.05) which is 2,100. This shows that tcount = 4.28>ttable = 2.100. On the basis of these calculations, the alternative hypothesis (Ha) which reads there is the influence of group guidance services with self management techniques to develop self-regulation ability of class VIII students of Muhammadiyah 3 Semarang Middle School in 2017/2018 academic year received the truth at 5% significance level. Thus, it shows that group guidance services with self managementtechniques can develop self-regulation skills of eighth grade students of Muhammadiyah 3 Middle School SemarangKeywords: Group Guidance, Self Management Techniques, Self Regulation